PENGARUH MODEL PEMBELAJARAN SINTETIK DENGAN BAHAN AJAR GAMIFIKASI: KEMAMPUAN KOMUNIKASI MATEMATIS (SELF-EFFICACY) - Cindy Safitri; Ruhban Maskur; Rizki Wahyu Yunian Putra; Nurhasanah Lenni; Ahmad Sodiq (ITB AAS INDONESIA Surakarta, 2021)
This research aims to know the influences of synthetic learning model assisted by gamification teaching materials on mathematical communication skills in terms of Self-Efficacy. This research is kind of Quasy Experiment Design by adopting Posttest Only Control Design. The technique sampling is taken by Non Probability Sampling using Porposive Sampling technique. The researcher used ANOVA (one way in different cells) in calculating the data. The result of this research showed that there is an influence of synthetic learning model assisted by gamification teaching materials on mathematical communication skills in terms of Self-Efficacy, students communication ability using gamification were better than conventional technique. In addition, there is an influence between Self-Efficacy(high, medium, and low) on students’ mathematical communication. Futhermore, there is no interaction between synthetic learning model by using gamification in terms of Self-Efficacyon students’ mathematical communication skills. Keywords: Synthetic Learning Model, Gamification Self-Efficacy